Pengaruh Maraknya Judi Online Terhadap Pengelolaan Keuangan di Kalangan Mahasiswa: Studi Kasus: Mahasiswa Universitas Negeri Medan - Hapni Laila Siregar; Diana Puspita Ayu; Hanifah Hanum; May Sartika; Silvia Annur Hasibuan (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The purpose of this research is to examine how Medan State University students' financial management is affected by the widespread practice of online gambling.  The increasingly accessible online gambling phenomena has led to a number of issues, particularly with regard to the personal financial situation of students.  60 students were chosen as a sample for this study, which used a quantitative approach with a survey methodology.  With the use of SPSS 25 software and basic linear regression, data analysis was completed. The purpose of this research is to examine how Medan State University students' financial management is affected by the widespread practice of online gambling.  The increasingly accessible online gambling phenomena has led to a number of issues, particularly with regard to the personal financial situation of students.  60 students were chosen as a sample for this study, which used a quantitative approach with a survey methodology.  With the use of SPSS 25 software and basic linear regression, data analysis was completed.